The effect of pre-etching with 37% orthophosphoric acid on the shear bond strength of orthodontic brackets bonded using self-etching primer-adhesive system - Shaheen Hamdani; G Anita; Javed Sodawala; Sumit Gandhi; Sayyed Muhammad Ali (Wolters Kluwer Medknow Publications, 2016)
Objectives: The purpose of this study was to compare the effect of pre-etching with 37% orthophosphoric acid on the shear bond strength (SBS) of orthodontic brackets bonded using self-etching primer (SEP). Materials and Methods: Two hundred freshly extracted human premolars were divided randomly into two groups based on pre-etching with 37% orthophosphoric acid: Group 1 (control, n = 50) without pre-etching and Group 2 (experimental, n = 150) with pre-etching. Group 2 was further divided into three sub groups 2a, 2b, and 2c with 50 teeth each and was first pre-etched with 37% orthophosphoric acid for 10, 30, and 60 s, respectively. Brackets were bonded on the teeth in both the groups using SEP and light cure adhesive. The SBS were determined using universal testing machine. The comparison of SBS was done using one-way analysis of variance and Tukey's honest significant difference test. Results: The SBS of experimental Group 2 was significantly higher than the control Group 1 (p < 0.0001). Further, the SBS of Group 2a was highest, followed by Group 2b and 2c (p < 0.0001). Conclusion: It was found that pre-etching for 10 s prior to application of SEP-adhesive system increases the SBS of orthodontic brackets.